Dwarfism: Accessibility of Somatropin Therapy for Patients with Growth Hormone Deficiency and Impact of its Cost on the State Budget in Ukraine - Ivko, Tanya (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Dwarfism is rare diseases with prevalence 1.1 per 10,000 children population in Ukraine. Considering the high cost of the treatment and its duration, it is very important to study socioeconomic accessibility therapy and its impact on the state budget. The purpose was scientific generalization of the results of the study of socioeconomic accessibility and its impact on the state budget. The Material of the Study: Pharmaceutical market of somatropin; Anatomical Therapeutic Chemical (ATC)/defined daily dose (DDD) index; the data of the state register of wholesale selling prices of August 09, 2017; the data of average salary; and the data of state statistics service. Research Methods: Analysis of the pharmaceutical market of somatropin, ATC/DDD methodology, liquidity ratio of price Cliq, and solvency adequacy ratio Ð¡a.s, budget impact analysis. Results and Discussions. ATC/DDD methodology showed that the cost of DDD of somatropin ranged from 65.05 to 546.09 UAH. Liquidity ratio of price Cliq was 7.39, so price fluctuations were 739% of somatropin in the pharmaceutical market. Solvency adequacy ratio Ð¡a.s varied from 44.1 tÐ¾ 370.6 which indicated a fluctuation in the cost of treatment from 44.1 to 370.6% of the salary of the population. It is established that the possible impact on the budget of Ukraine in context of the cost of somatropin analogues ranges from 20965289.75 to 176002076.6 UAH per year. Budget savings can be 155036786.85 UAH per year using the cheapest analogues of somatropin. Conclusions: Somatropin therapy for the Ukrainian population is economically inaccessible, and this makes a significant burden on the state budget of Ukraine.